Influence of hydrogen on formation of primary structures of tin and aluminium bronze - E. I. Marukovich; V. Y. Stetsenko; A. V. Stetsenko (Литьë и металлургия, 2023)
It is shown that hydrogen is a demodifying element of primary structures of tin and aluminum bronzes during their crystallization. The mechanism of influence of hydrogen on the formation of primary structures of tin and aluminum bronzes can be explained from the position of nanostructured crystallization of casting alloys. Hydrogen atoms adsorbed on elementary nanocrystals in melts prevent the combination of nanocrystals into nuclei of crystallization of microcrystals α‑phases of tin and aluminum bronzes. The result is castings with unmodified primary structures. The modifiers reduce the concentration of adsorbed hydrogen in the melts of tin and aluminum bronzes. This results in the milling of the primary phase microcrystals in the castings as they solidify.